Quantum dots in nanomedicine: Recent trends, advances and unresolved issues - VOLKOV, YURI (My University, 2015)
The review addresses the current state of progress in the use of ultra-small nanoparticles from the category of quantum dots (QDs), which presently embraces a widening range of nanomaterials of different nature, including “classical” semiconductor groups III-V and II-VI nanocrystals, along with more recently emerged carbon, silicon, gold and other types of nanoparticles falling into this class of nanomaterials due to their similar physical characteristics such as small size and associated quantum confinement effects. A diverse range of QDs applications in nanomedicine has been extensively summarised previously in numerous publications. Therefore, this review is not intended to provide an all-embracing survey of the well documented QDs uses, but is rather focused on the most recent emerging developments, concepts and outstanding unresolved problematic and sometimes controversial issues. Over 125 publications are overviewed and discussed here in the context of major nanomedicine domains, i.e. medical imaging, diagnostics, therapeutic applications and combination of them in multifunctional theranostic systems.
PUBLISHED
Export Date: 22 August 2015 Article in Press
Keywords: Quantum dots; Nanomedicine; Nanoparticles; Medical imaging; Diagnostics; Theranostics; Quantum dots; Nanomedicine; Nanoparticles; Medical imaging; Diagnostics; Theranostics